Perancangan Alat Identifikasi Wajah Dengan Algoritma You Only Look Once (YOLO) Untuk Presensi Mahasiswa - Irma Salamah; M. Redho Ali Said; Sopian Soim (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Presence is an important thing in educational world especially higher education. One of students’ success keys is in their presence because it has correlation to the learning quantity carried out by a college student. Some colleges whose learning conducted face to face still use conventional way by using attendant list sheet until this system is felt less effective in the middle of digitalization development marked by the increase of technology usage. Face recognition attendance technology is a technology which can be adapted from one of artificial intelligence science namely machine learning. Machine learning with deep learning branch becomes the solution which eases human’s work. In its process, face recognition requires certain accurate face detection with certain algorithm. In this research, the method used was You Only Look Once (YOLO) algorithm where to follow some research which had been conducted previously it has high accuracy in face prediction. The test results obtained an average accuracy of 0.9793 by paying attention to parameters such as lighting and real-time sending to the website. Through this research, it is hoped that the attendance process will be more effective and can be monitored by lecturers.